Detection of Insertion/Deletions (InDel) Within Five Clock Genes and Their Associations with Growth Traits in Four Chinese Sheep Breeds - Ziteng Wang; Xiaohua Yi; Mengzhe Yang; Xiuzhu Sun; Shuhui Wang (Veterinary Sciences)
Organisms have the capacity to detect day–night fluctuations through oscillators regulated by circadian clock genes, which are crucial for regulating various biological processes. Numerous studies have demonstrated a marked association between these genes and various growth traits of sheep. This study identified polymorphisms at 23 potential loci within five clock genes in four Chinese sheep breeds. Only two polymorphic insertion/deletions (InDels) were detected in CLOCK and PER3 genes, respectively. The distribution of these two loci in four Chinese sheep breeds and their association with growth traits were further explored. A 12 bp deletion was found in the intron of the CLOCK gene (rs604230640), which was significantly associated with body height (p < 0.05), body oblique length (p < 0.05) and cannon girth (p < 0.05) in Hu sheep (HS). A 22 bp insertion in the intron of the PER3 gene (rs600537720) with a dominant genotype of insertion/insertion (II) was found to have a significant association with chest depth (p < 0.05) in Small-Tail Han sheep (STHS), tail width (p < 0.05) in Tong Sheep (TS), and in Lanzhou fat-tailed sheep (LFTS). In conclusion, this study has elucidated the polymorphisms of CLOCK and PER3 genes and has examined the influence of these two genes on the growth traits of sheep. Concurrently, the two molecular markers identified in CLOCK and PER3 could potentially serve in the marker-assisted selection of growing-related traits in local Chinese sheep breeds.